Preparation and Characterization of UV-Cured Hybrid Polyvinyl Alcohol Nanofiber Membranes by Electrospinning - (:unkn) unknown (UNIV FED SAO CARLOS, DEPT ENGENHARIA MATERIALS, 2014)
The present study investigated the possibility of preparing polyvinyl alcoholic (PVA) organic-inorganic hybrid nanofiber membranes by electrospinning with UV irradiation. To this end, PVA, PVA/SiO2 organic-inorganic hybrid obtained with Geniosil (R) XL 33 as a SiO2 source, and imidazole-functionalized mesoporous PVA/SiO2/N=N nanofiber membranes were synthesized. These membranes were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, thermogravimetric-differential thermal analysis, and Brunauer-Emmett-Teller analysis. According to results, fine polymeric nanofibers were obtained in the size range of 100-200 nm for pure PVA nanofibers and 150-250 nm for PVA/SiO2 hybrid nanofibers, while imidazole-functionalized PVA/SiO2 nanofibers were less than 100 nm. The membranes produced are suitable for use in various applications, including filtration and adsorption, in the biomedical and textile industries, among others.
Keywords: electrospinning; nanofiber; UV-curable; hybrid material; polyvinyl alcohol; POLY VINYL ALCOHOL; METAL-IONS; POLY(VINYL; NANOPARTICLES; FABRICATION; COMPOSITE; FIBERS; WATER; MATS